Preparation And Characterization Of Zeolite Y – Based Catalyst For Sonocatalytic Degradation Of Organic Dyes In Water - Alwash, Atheel Hassan (2013)
Sonocatalytic process was adopted to enhance the decolorization and mineralization of wastewater containing dyes (amaranth, reactive blue 4 and congo red). Zeolite Y was used as the support material and modified using three different active metals i.e. Ti, La and Fe. The position of titanium oxide (either encapsulated or loaded on the support) was controlled using different preparation methods, e.g. ion exchange and impregnation methods. Meanwhile, La or Fe metals were deposited on the external surface of the zeolite. The modification of the encapsulated TiO2 by Fe metal enhanced the decolorization efficiency of amaranth dye more efficiently than its modification with La metal. The maximum decolorization efficiency was about 97 % with maximum COD removal of 57 % after 120 min of reaction. The catalytic reaction was assisted by an ultrasonic irradiation source at 50 W for the output power and the frequency was 40 kHz. As the position of TiO2 was replaced to be at the external surface of zeolite together with Fe metal, the catalyst also showed higher decolorization efficiency of amaranth about 100 % after 120 min of sonocatalytic reaction. All catalytic efficiencies of the modified catalysts were demonstrated by comparing their catalytic activity with that of bare zeolite and mono-doping of active metal with zeolite under the same experimental conditions. Different operational parameters were investigated for the best of higher catalytic activity such as initial pollutants concentration, initial pH, catalyst loading and the addition of oxidizing agents such as H2O2. Among various reaction conditions, the initial pH greatly influenced the sonocatalytic process in all cases.